Improved outcome of COVID-19 over time in patients treated with CAR T-cell therapy: Update of the European COVID-19 multicenter study on behalf of the European Society for Blood and Marrow Transplantation (EBMT) Infectious Diseases Working Party (IDWP) and the European Hematology Association (EHA) Lymphoma Group - Spanjaart, Anne Mea; Ljungman, Per; Tridello, Gloria; Schwartz, Juana; Martinez-Cibrián, Nuria; Barba, Pere; Kwon, Mi; Lopez-Corral, Lucia; Martinez-Lopez, Joaquin; Ferra, Christelle; Di Blasi, Roberta; Ghesquieres, Hervé; et al. (Leukemia, 2024)
COVID-19 has been associated with high mortality in patients treated with Chimeric Antigen Receptor (CAR) T-cell therapy for hematologic malignancies. Here, we investigated whether the outcome has improved over time with the primary objective of assessing COVID-19-attributable mortality in the Omicron period of 2022 compared to previous years. Data for this multicenter study were collected using the MED-A and COVID-19 report forms developed by the EBMT. One-hundred-eighty patients were included in the analysis, 39 diagnosed in 2020, 35 in 2021 and 106 in 2022. The median age was 58.9 years (min-max: 5.2-78.4). There was a successive decrease in COVID-19-related mortality over time (2020: 43.6%, 2021: 22.9%, 2022: 7.5%) and in multivariate analysis year of infection was the strongest predictor of survival (p = 0.0001). Comparing 2022 with 2020-2021, significantly fewer patients had lower respiratory symptoms (21.7% vs 37.8%, p = 0.01), needed oxygen support (25.5% vs 43.2%, p = 0.01), or were admitted to ICU (5.7% vs 33.8%, p = 0.0001). Although COVID-19-related mortality has decreased over time, CAR T-cell recipients remain at higher risk for complications than the general population. Consequently, vigilant monitoring for COVID-19 in patients undergoing B-cell-targeting CAR T-cell treatment is continuously recommended ensuring optimal prevention of infection and advanced state-of-the art treatment when needed.
Keywords: výsledek terapie; Young Adult; Male; Child, Preschool; Middle Aged; Survival Rate; hematologické nádory; Immunotherapy, Adoptive; mladý dospělý; Adolescent; Hematologic Neoplasms; Child; Europe; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; SARS-CoV-2; mladiství; Treatment Outcome; Evropa; předškolní dítě; lidé; ženské pohlaví; Humans; imunoterapie adoptivní; chimerické antigenní receptory; Female; lidé středního věku; míra přežití; COVID-19; Receptors, Chimeric Antigen